Responsibility of Land Deed Officials (Ppat) in Providing Unfinished Name Transfer Services - Parhan, Parhan; Fajar Riyanto, Taufan (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine the responsibility of the Land Deed Official (PPAT) for unfinished name change services and to determine the legal consequences of unfinished name change services. This study uses a type of sociological or empirical legal research that includes legal identification and legal effectiveness, empirical legal research is legal research where data is obtained through primary legal data or data obtained directly in the community. Based on the research conducted, it can be seen that the responsibility of the PPAT includes Civil, Criminal, Administrative, and PPAT Code of Ethics obligations. If the Deed has been carried out in accordance with the procedure and there is a delay caused by the negligence of the PPAT, then in practice the PPAT can be sued for compensation for the delay if the delay causes losses to the parties. The legal consequences of the transfer of Land Rights that are registered late are that the Deed cannot be registered for the Transfer of Rights at the National Land Agency Office and this is the personal responsibility of the PPAT because the PPAT is obliged to comply with the registration period for the transfer of Rights, which is a maximum of seven working days from the signing of the Deed. PPAT itself can be subject to administrative sanctions in the form of a written warning and in serious cases PPAT can be dismissed from his position. And if force majeure occurs, PPAT cannot be sued because it is beyond the fault of PPAT as long as all procedures required by the National Land Agency have been fulfilled.Keywords: Effectiveness; Empirical; Legal; Responsibility.